The return of the gift: European history of a global idea - Liebersohn, Harry (Cambridge University Press, 2011)
"This book is a history of European interpretations of the gift from the mid seventeenth to the early twentieth century. Reciprocal gift exchange, pervasive in traditional European society, disappeared from the discourse of nineteenth-century social theory only to return as a major theme in twentieth-century anthropology, sociology, history, philosophy and literary studies. Modern anthropologists encountered gift exchange in Oceania and the Pacific Northwest and returned the idea to European social thought; Marcel Mauss synthesized their insights with his own readings from remote times and places in his famous 1925 essay on the gift, the starting-point for subsequent discussion. The Return of the Gift demonstrates how European intellectual history can gain fresh significance from global contexts"--Provided by publisher